Guidelines for safe and reliable instrumented protective systems (CCPS guidelines series., 2007)
This book explains the decision-making processes for the management of instrumented protective systems (IPS) throughout a project's life cycle. It uses the new IEC 61511 standard as a basis for the work processes used to achieve safe and reliable process operation. By walking the reader through a project's life cycle, engineering, maintenance, and operations, the information allows users to easily focus on their responsibilities and duties. Using this approach, the book is useful as a primer, guidelines reference, and resource manual. Examples provide the added "real-world" experienc